Implementation of Teacher Development Policy In Increasing The Quality of State Aliyah Madrasah In Langkat District - Sudirman, Sudirman; Wijaya, Candra; Sit, Masganti (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study seeks to reveal and analyze the following: 1) What is the formulation of teacher development policy planning in improving the quality of public Madrasah Aliyah in Langkat Regency? 2) How is the process of implementing teacher development policies in improving the quality of State Aliyah Madrasas in Langkat Regency communicated? 3) How do stakeholders support the implementation of teacher development policies in improving the quality of State Aliyah Madrasas in Langkat Regency? This study employs a multisite qualitative method, with data collection techniques such as interviews, observation, and document studies, while the researcher refers to the data validity standard proposed by Lincoln and Guba, which consists of credibility, transferability, dependability, and comfirmability, to strengthen the validity of the data findings and the authenticity of the research. The findings of this study show that: 1) Madrasa heads implement teacher development policies to improve the quality of Madrasahs through teacher professional development programs such as: Teacher qualification improvement programs or advanced study programs, Equalization and Certification Programs, Competency-based Integrated Training Programs, and Supervision Programs; and 2) The process of communication in implementing teacher development policies to improve the quality of Madrasahs. The implementation of teacher development policies to improve quality must also be accompanied by good commitment from all madrasah members, including teachers, and high awareness, as well as organizing an efficient bureaucracy, making the vision and mission of madrasas the basis for the development and development of madrasa culture, and good managerial activities and innovative; 3) Stakeholder support in implementing teacher development policies to improve Madrasah quality. The madrasah committee, local government, parents of students, and the surrounding community, who are very good at assisting policies in accordance with the direction of development, supporting all activities carried out by the madrasa; and 4) The teacher development model in improving the quality of State Madrasah Aliyah in Langkat Regency is reflected through activities to improve coordination between madrasa heads, Head of Madrasah Education